Answer: ans= y=1 (please look at the step by step explanation) Step-by-step explanation: 2x-2y=2 2x-(2x-3)=2 2x-2x+3=2 2x-2+3=2 0+3=2 therefore, y=2x-3 2x-2y=2 2x-2(2x-3)=2 2x-4x+6=2 -2x+6=2 -2x=6 -2x-2y therefore x=y/-2= -2/ y=2x-3 y=2 multiplied by 2 -3 y=y-3 Log in to Reply

Answer: ans= y=1 (please look at the step by step explanation)Step-by-step explanation: 2x-2y=22x-(2x-3)=22x-2x+3=22x-2+3=20+3=2therefore, y=2x-32x-2y=22x-2(2x-3)=22x-4x+6=2-2x+6=2-2x=6-2x-2ytherefore x=y/-2= -2/y=2x-3y=2 multiplied by 2 -3y=y-3